Mangupa; An Oral Tradition of Angkola Community - Yusni Khairul Amri (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
The oral traditions of indigenous communities Angkola  mangupa belief to be efforts to restore stamina to the body (paulak tondi tu badan) to seek blessings from Allah, the Almighty God, to be safe, healthy, and prosperous in life. Mangupa levels adjusted corresponding to pangupa materials such as buffalo, goats, chickens, and eggs, then given advice mangupa (hata pangupa; hata upah-upah) submitted by traditional leaders. The analysis results of mangupa found the local knowledge values such as: a) the human relationship with God, b) the meaning of human life, c)  the human relationship with the natural surroundings, d) the human relationship with time, e) the behavior to be industrious and enterprising, thrifty, and religious, to get along peacefully with each other; f) the aesthetic value of humility, customary of politeness, g) the expectation that the marriage will be the  marriage of a lifetime; h) The value and philosophical significance of indigenous material derived pangupa animals, plants, and derived from nature; i) The bride and groom who have not through a traditional ceremonies (maradat) retains the customary effect throughout the traditional debt to be paid until they have the means.